Pengaruh Good Corporate Governance, Firm Size, dan Independensi Auditor terhadap Integritas Laporan Keuangan - Deski Arivan; Hermie Hermie (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Management of a business must always be carried out with the aim of advancing the interests of the company, and this is what is meant by